Bite wound and mauling of a zookeeper by a gorilla - Jinsuke Mizuno; Takahiro Hiruma; Ichiro Hirayama; Miyuki Yamamoto; Takehiro Matsubara; Kent Doi (Trauma Case Reports, 2023)
The majority of bite wounds that we encounter in the emergency department are caused by dogs, cats and humans, but bite injuries can be caused by a variety of animals. Here, we describe a case of bite wound and trauma caused by a large gorilla (Western lowland gorilla) weighing over 170 kg. Gorilla bites are rare, and the patient had an open fracture of the right distal radioulna in addition to multiple bite wounds. Treatment required careful consideration of gorilla antigenicity and a literature review to guide the selection of appropriate antimicrobial agents. Furthermore, trauma inflicted by large animals tends to require systemic traumatological screening, and patients can develop acute stress disorder because of a fear of being attacked again; therefore, early psychiatric intervention is important.